2016
DOI: 10.3892/ol.2016.5395
|View full text |Cite
|
Sign up to set email alerts
|

The effect of miR-146a on STAT1 expression and apoptosis in acute lymphoblastic leukemia Jurkat cells

Abstract: The effect of miR-146a-dependent regulation of STAT1 on apoptosis in acute lymphoblastic leukemia (ALL) Jurkat cells was investigated. The miR-146a mimic and miR-146a inhibitor vectors were constructed in vitro, and experimental grouping was as follows: Control group (untreated Jurkat cells), empty vector group (Jurkat cells transfected with empty vector), agonist group (Jurkat cells transfected with miR-146a mimic) and the inhibitor group (Jurkat cells transfected with miR-146a inhibitor). Western blot analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Has-mir-130a was involved in the megakaryocytic differentiation and erythropoiesis, and its expression was also related to the differentiation patterns in AML [12]. Has-mir-146a was a regulator of apoptosis [13], and its expression was associated with patient prognosis of AML. The increase of has-mir-146a can enhance the sensitivity of leukemic blast cells to cytotoxic drugs [14].…”
Section: Discussionmentioning
confidence: 98%
“…Has-mir-130a was involved in the megakaryocytic differentiation and erythropoiesis, and its expression was also related to the differentiation patterns in AML [12]. Has-mir-146a was a regulator of apoptosis [13], and its expression was associated with patient prognosis of AML. The increase of has-mir-146a can enhance the sensitivity of leukemic blast cells to cytotoxic drugs [14].…”
Section: Discussionmentioning
confidence: 98%
“…In particular, an overexpression of the mir-146 gene was observed. miR-146 can regulate the expression of the apoptosis factor STAT1, and the anti-apoptosis factor Bcl-xL, thus promoting the apoptosis of ALL cells [44]. Furthermore, tumour protein P63 gene (TP63 gene) was also upregulated in E/R KO clones as compared with control clones.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Through our literature review, we found some influential review focused on miRNAs in childhood ALL have mentioned miR-100, miR-210, and miR-146a in common. 8,9 In the present study, we focused on genetic variants of miR-100, miR-146a, and miR-210, which were all demonstrated to be participate in carcinogenesis of ALL, 13,14,16 and investigated their association with susceptibility of childhood ALL. Among them, rs7395206 have never been reported in other studies while rs543412 and rs2910164 has not been detected in Chinese childhood ALL groups.…”
Section: Discussionmentioning
confidence: 99%